2018
DOI: 10.1038/modpathol.2017.123
|View full text |Cite
|
Sign up to set email alerts
|

Transplant glomerulopathy

Abstract: In the renal allograft, transplant glomerulopathy represents a morphologic lesion and not a specific diagnosis. The hallmark pathologic feature is glomerular basement membrane reduplication by light microscopy or electron microscopy in the absence of immune complex deposits. Transplant glomerulopathy results from chronic, recurring endothelial cell injury that can be mediated by HLA alloantibodies (donor-specific antibodies), various autoantibodies, cell-mediated immune injury, thrombotic microangiopathy, or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 152 publications
(171 reference statements)
3
59
0
1
Order By: Relevance
“…The result of the present study underscored that severe baseline interstitial chronic changes (ci + ct) and cg at biopsy were predictors of unfavorable allograft prognosis in TG patients even after taking into consideration clinical characteristics. TG is not a specific diagnosis but rather a pattern of endothelial injury with at least 3 well-documented overlapping etiologies that included AMR, thrombotic microangiopathy, and chronic HCV infection-associated glomerular lesions [6,13,14]. In line with previous reports [13], the current study also demonstrated the striking prevalence of HCV infection in recipients with TG (21.1%), which was significantly higher than the prevalence seen in the non-TG patients (7.0%) [15].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The result of the present study underscored that severe baseline interstitial chronic changes (ci + ct) and cg at biopsy were predictors of unfavorable allograft prognosis in TG patients even after taking into consideration clinical characteristics. TG is not a specific diagnosis but rather a pattern of endothelial injury with at least 3 well-documented overlapping etiologies that included AMR, thrombotic microangiopathy, and chronic HCV infection-associated glomerular lesions [6,13,14]. In line with previous reports [13], the current study also demonstrated the striking prevalence of HCV infection in recipients with TG (21.1%), which was significantly higher than the prevalence seen in the non-TG patients (7.0%) [15].…”
Section: Discussionsupporting
confidence: 71%
“…It has been demonstrated that impaired allograft function (decreased estimated glomerular filtration rate [eGFR]) and increased proteinuria at the time of allograft biopsy served as clinically important predictors of adverse outcomes [5,6]. Nevertheless, studies focusing on histologic features' impact on TG survival are scarce and it remains unknown whether histologic alterations observed in TG provide additional prognostic value in addition to clinical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of glomerular capillary remodeling alone is not pathognomonic in TG. Duplication of GBMs is also observed in recurrent membranoproliferative glomerulonephritis, hepatitis C virus infection, and thrombotic microangiopathy in renal allografts (4,9). cells of glomerular capillaries and PTCs are important as pathological changes of early-stage ABMR (3,6,21).…”
Section: Abmr Group -Other Ultrastructural Changesmentioning
confidence: 99%
“…It is sometimes difficult if not impossible to ascertain the exact etiology for TG in an individual case. Regardless of the underlying etiology, endothelial cell injury and subsequent remodeling has been demonstrated to be the essential pathophysiology for the formation of double contours in TG [1].…”
Section: Introductionmentioning
confidence: 99%
“…Transplant glomerulopathy (TG), which is histologically characterized by double contours of the glomerular basement membrane (GBM) without concomitant immuno-complex deposition, is a histomorphologic pattern frequently seen in patients presented with late allograft dysfunction several years or decades after kidney transplantation [1,2]. Although it has been elucidated that chronic antibody-mediated rejection accounts for the majority of cases with a morphologic diagnosis of TG, other pathoetiologies such as hepatitis C virus (HCV) infection and thrombotic microangiopathy (TMA) could also incur allograft chronic injury with a morphologic manifestation of TG [3].…”
Section: Introductionmentioning
confidence: 99%